Laboratory validation of buried piezoelectric scour sensing rods. Issue 9 (2nd December 2016) - Azhari, Faezeh; Loh, Kenneth J.
Summary: Scour, or the erosion of soil and sediments near bridge piers and abutments, accounts for the majority of overwater bridge failures. This study focuses on evaluating the use of a driven piezoelectric scour sensing rod, where the real‐time dynamics of the voltage response of the sensing rod is used to determine scour depths using the inverse relation between natural frequency and the rod's exposed length. A poly (vinylidene fluoride) polymer strip forms the main sensing component of this prototype sensor. After confirming the viability of the sensing concept through various idealized tests, the response of the sensors was studied in scour conditions simulated in a laboratory flume. The sensors were driven into the soil surrounding a cylindrical pier. As the scour hole evolved, the exposed length of the sensors changed, causing the measured natural frequencies to also vary. Scour depth at each sensor location was determined using a simple cantilever beam eigenfrequency analysis where the soil support fixity was modeled with a rotational spring. The results were promising in that the sensors were capable of detecting scour depths and the scour hole topography with reasonable accuracy. As is the case with other rod‐like scour sensors, vulnerability to debris and installation difficulties are some of the limitations that need to be addressed in future real‐world implementations.